The Role of Social Existence in Improving the Quality of Life of People with Disabilities: Perspectives of Involvement, Acceptance, and Social Participation - Saputri, Toviyani Widi; Astuti, Budi (Journal of Education Reseach and Evaluation, 2025)
This research identifies persistent barriers to social rejection and discrimination that continue to limit opportunities for participation and acceptance in society. This study investigates how specific dimensions of social presence, namely social engagement, social acceptance, and participation opportunities, affect the quality of life of individuals with disabilities. The study used a quantitative descriptive approach by collecting data from 30 students with disabilities through a structured questionnaire measuring social engagement, social acceptance, and participation opportunities. Data analysis was conducted using descriptive and inferential statistics, including Pearson correlation and simple linear regression, to assess the predictive power of social presence on quality of life. The results revealed a significant positive relationship between higher levels of social presence and improved quality of life, with social engagement emerging as the strongest predictor among the measured variables. Interventions targeted at increasing social participation and reducing discrimination can significantly improve the well-being of people with disabilities in society. This research makes an empirical contribution to the literature on disability and social inclusion. It offers evidence-based evidence for developing policies and intervention programs more responsive to the social needs of people with disabilities.